2011
DOI: 10.1111/j.1365-2788.2011.01403.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of disability on families: grandparents' perspectives

Abstract: Grandparents are central to family functioning and quality of life, but this contribution comes with a significant cost to their own personal well-being. Implications for policy, practice and research are discussed, particularly grandparents' fear that their family could not cope without their support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 14 publications
3
19
0
12
Order By: Relevance
“…It is reasonable to assume that these grandparents may therefore refrain from adding to their children's burden by expressing criticism or personal distress. This is in line with the study by Miller et al (2012), who reported that a main theme raised by grandparents was ''holding their emotions.'' According to those authors, grandparents felt that the best way to help their children was to suppress their own emotions and to express positivity, regardless of their own distress and sorrow.…”
Section: Differences Between Grandparents Of Children With Disabilitisupporting
confidence: 91%
See 2 more Smart Citations
“…It is reasonable to assume that these grandparents may therefore refrain from adding to their children's burden by expressing criticism or personal distress. This is in line with the study by Miller et al (2012), who reported that a main theme raised by grandparents was ''holding their emotions.'' According to those authors, grandparents felt that the best way to help their children was to suppress their own emotions and to express positivity, regardless of their own distress and sorrow.…”
Section: Differences Between Grandparents Of Children With Disabilitisupporting
confidence: 91%
“…Despite increasing awareness of the impact of disabilities in children on the nuclear and extended family, little is known about their effects on intergenerational relations in general or on grandparents in particular (Hastings, Thomas, & Delwiche, 2002;Hillman, 2007;Miller, Buys & Woodbridge, 2012;Mitchell, 2007Mitchell, , 2008. The grandparenting role can be unique and meaningful, as grandparenthood can offer a symbolic sense of immortality, a link between history and the future, and compensation for past disappointments.…”
Section: Stress Among Grandparents Of Children With Intellectual Disamentioning
confidence: 96%
See 1 more Smart Citation
“…Ramaglia et al [17] reported that in Italy, 8% of the care burden is attributed to grandparents. Similarly, in Australia, grandparents who live relatively close to the nuclear family are included in taking care of their child with special needs, supporting family functioning and quality of life [43]. In our study, because of the involvement of other members of the extended family in child care, it is possible that parents perceive that their child is less competent and, therefore, are more restrictive in terms of various activities.…”
Section: Variablementioning
confidence: 95%
“…The necessity of taking care of the child, when societal resources are limited or absent, everyday caregiving and responsibilities affect the individual family' member opportunities (further on education, get job, etc.). Social capital becomes a crucial source for low income families (Miller, Buys & Woodbridge, 2012). Habilitation family resources from sociological theories mean family intentionality to influence the habilitation process, strengthening / building different forms of family capital.…”
Section: Habilitation Resources: Theoretical Implicationsmentioning
confidence: 99%